Effective Street Geometry and Shading Strategies for Pedestrian Thermal Comfort: A Scenario Based Simulation Approach - Mohite, Shivanjali; Surawar, Meenal (Geographica Pannonica, 2026)
The development of urban heat issues poses significant challenges for pedestrians in tropical cities, necessitating climate-responsive street design. This study employs a scenario-based simulation approach to determine optimal combinations of street geometry and shading strategies that enhance Pedestrian Thermal Comfort (PTC). Using ENVI-met, this study simulated 90 scenarios by combining geometric variables, such as aspect ratio (AR), building typology (BT), and street orientation, with five shading strategies in Nagpur City, India. The modified Physiological Equivalent Temperature (mPET) index was calculated for each scenario using a pre-trained machine learning model. Results quantified that canopy shading was the most effective strategy, reducing mPET by up to 7°C in E-W streets. The effective street geometric combination was a N-S oriented street with a deep AR and linear BT, which consistently achieved the lowest mPET values (33.1–35.8°C). The study concludes with a rating matrix that guides the integration of shading design with street geometry to achieve thermally resilient streets.
Keywords: Pedestrian Thermal Comfort; Urban Street Geometry; ENVI-met; Machine Learning; Microclimate